A Time Difference of Arrival System Architecture for GSM Mobile Phone Localization in Search and Rescue Scenarios - Götz, Alexander; Zorn, Stefan; Rose, Richard; Fischer, Georg; Weigel, Robert (Workshop on Positioning, Navigation and Communication (WPNC), 2011)
In this work, a novel architecture of a time difference of arrival based localization system for GSM mobile phones is proposed. The system is well-suited for search and rescue scenarios and comprises receiving stations for GSM signals, a dedicated GSM base station and a radio frequency jamming system for GSM and UMTS signals. The system may be operated in the E-GSM 900 band providing high penetration of the covering debris material and a sufficient overall bandwidth for the time difference of arrival measurements. In this case, the best attainable accuracy of localization is shown to be in the scale of 5 m. The components of the system are described in more detail and possible implementations are proposed. The system may also be applied for the localization of UMTS mobile phones making use of the integrated GSM functionality. The proposed system represents a novel approach for time difference of arrival based localization of mobile phones in search and rescue scenarios.
elib2cris::1512001600,goetz2011
Keywords: GSM; Localization; TDOA